2021
DOI: 10.1007/s11255-021-02908-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and predictors of failure of arteriovenous fistulae for hemodialysis

Abstract: Purpose Arteriovenous fistula(AVF) is preferred vascular access for hemodialysis but has primary failure in 20–60%. Studying predictors of AVF failure would help plan appropriate management.We studied AVF outcomes, clinical and vascular factors predicting their failure in patients requiring hemodialysis. Methods Retrospective study of patients with AVF creation from January 2017 to December 2018. Outcomes studied were immediate (< 72 h), primary (3 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 20 publications
1
12
2
Order By: Relevance
“…A study conducted in India found a comparable finding that the primary AVF failure rate associated with interventional nephrologists was 16.6% (83/500, 95%CI: 13.6–20.11%) [ 26 ]. However, our rate was lower than that of another Indian study in which the reported rate was 25.6% (90/352, 95%CI: 21.3–30.4%) due to the differences in the definitions of primary AVF failures [ 33 ]. In the latter Indian study, primary failure was defined as an inadequate AVF obtained 3 months after the operation compared to a 6-week period in our study [ 33 ].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…A study conducted in India found a comparable finding that the primary AVF failure rate associated with interventional nephrologists was 16.6% (83/500, 95%CI: 13.6–20.11%) [ 26 ]. However, our rate was lower than that of another Indian study in which the reported rate was 25.6% (90/352, 95%CI: 21.3–30.4%) due to the differences in the definitions of primary AVF failures [ 33 ]. In the latter Indian study, primary failure was defined as an inadequate AVF obtained 3 months after the operation compared to a 6-week period in our study [ 33 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Firstly, it could be due to our strict selection of study participants, especially a requirement of both arterial and venous diameters of more than 2 mm. Indeed, the arterial diameter is an important predictor for AVF maturation with an arterial diameter of < 2.0 mm highly associated with primary failure [ 33 ]. Secondly, the favorable outcome of AVF creations was also attributable to our considerably high rate of study participants who were well prepared for hemodialysis with AVF creations prior to the initiation of renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While endovascular and open surgical interventions are available to salvage AVFs that fail to mature and AVFs that suffer decreased flow rates over time, success rates for these salvage procedures are variable, their long-term durability is low, and the associated health care costs and burdens are necessarily increased [ 11 ]. Overall, approximately 20–60% of patients experience primary AVF failure, which underscores the need to explore strategies to improve AVF maturation and maintenance [ 12 ]. One such method is the suppression of venous neointimal hyperplasia (NIH), which interferes with AVF maturation.…”
Section: Arteriovenous Fistula Access For Hemodialysis Usementioning
confidence: 99%
“…We had a single case of a 65 year pa ent in this study so we cannot comment on the influence of age on fistula outcome at present. Other studies show propor on of diabetes in the range of 16.6%-50% and concludes its presence and pa ent age do not affect the [11][12][13] fistula outcome but shows be er outcome in male gender. This is similar to the outcome of the our study but the gender related outcome varia on can be due to small sample size in the current study.…”
Section: Discussionmentioning
confidence: 89%